Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah di Kantor Cabang BRI Rangkasbitung - Ferdian Arie Bowo; Ratu Neneng Rozbiati; Deni Setiawan (E-Journal Studia Manajemen, 2014)
The quality of service is good is very important in creating customer satisfaction, but to understand how to evaluate the quality received by consumers is not easy, the quality of services is more difficult to evaluate than the quality of goods, quality of service is not created through the production process in the factory to be submitted to consumers as quality goods. Many studies show that the percentage of customers who decided to continue to use certain bank services because the services they received no satisfaction or perceived well. This study aims to determine the effect of service quality on customer loyalty to the PT. Bank Rakyat Indonesia (Persero) Tbk, Branch Office Rangkasbitung. Respondents in this study as many as 60 people. The sampling using probability sampling method with simple random sampling and systematic sampling. The results show there is influence service quality and customer loyalty.